The impact of individual health on relative poverty: evidence from China - Ying Liu; Gongjing Gao; Yating Sun (Frontiers in Public Health)
BackgroundFollowing China’s historic achievement in eradicating absolute poverty, the focus of anti-poverty policies has shifted to alleviating relative poverty, with health status playing a pivotal role in sustainable poverty reduction.MethodsBased on the 2021 Chinese General Social Survey (CGSS 2021), we employed structural equation modeling (SEM) to analyze the relationship between individual health and relative poverty.ResultsThe analyses showed a significant negative correlation between individual health and relative poverty. This effect occurs in two ways: by increasing employment participation and by reducing the burden of health care expenditures. It is worth noting that health-induced income loss has a greater impact on relative poverty than direct medical costs.ConclusionThese findings demonstrate that health plays a dual role in poverty governance: enhancing human capital while mitigating economic risks. This provides empirical evidence for alleviating relative poverty and advancing common prosperity through improving individual health outcomes.